2024
DOI: 10.1111/nph.19603
|View full text |Cite
|
Sign up to set email alerts
|

The protein phosphorylation landscape in photosystem I of the desert algae Chlorella sp.

Guy Levin,
Michael Yasmin,
Tomasz Pieńko
et al.

Abstract: Summary The phosphorylation of photosystem II (PSII) and its antenna (LHCII) proteins has been studied, and its involvement in state transitions and PSII repair is known. Yet, little is known about the phosphorylation of photosystem I (PSI) and its antenna (LHCI) proteins. Here, we applied proteomics analysis to generate a map of the phosphorylation sites of the PSI–LHCI proteins in Chlorella ohadii cells that were grown under low or extreme high‐light intensities (LL and HL). Furthermore, we analyzed the cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…The proteomics analysis suggested that in addition to the robust downregulation of LHCII and marked accumulation of carotenoid in HL-grown cells (Levin et al, 2021;, SOD and GPX, and potentially CBR, play a role in considerably reducing ROS accumulation and oxidative damage in HL-grown cells. In agreement with this hypothesis, we have recently reported that HL-grown cells accumulate fewer PSI protein degradation products compared to LL-grown cells, suggesting they are better protected from oxidative stress (Levin et al, 2024).…”
Section: Hl-grown Cells Upregulate Cbr and Enzymatic Antioxidant Expr...supporting
confidence: 83%
See 1 more Smart Citation
“…The proteomics analysis suggested that in addition to the robust downregulation of LHCII and marked accumulation of carotenoid in HL-grown cells (Levin et al, 2021;, SOD and GPX, and potentially CBR, play a role in considerably reducing ROS accumulation and oxidative damage in HL-grown cells. In agreement with this hypothesis, we have recently reported that HL-grown cells accumulate fewer PSI protein degradation products compared to LL-grown cells, suggesting they are better protected from oxidative stress (Levin et al, 2024).…”
Section: Hl-grown Cells Upregulate Cbr and Enzymatic Antioxidant Expr...supporting
confidence: 83%
“…Chlorella ohadii is a green micro-alga that thrives in the desert, where it is exposed to extremely high light intensities (Treves et al, 2013; Levin et al, 2021). Accordingly, C. ohadii is highly tolerant to photoinhibition (Treves et al, 2016; Levin et al, 2023; Levin et al, 2024). It has been found that the adaptation of C. ohadii to HL involves marked changes in the thylakoids of which the most pronounced are the large size reductions in the PSII antenna, the LHCII, as well as the massive accumulation of carotenoids and several photoprotective proteins (Levin et al 2021, 2023).…”
Section: Introductionmentioning
confidence: 99%